Pengembangan Model Pemilihan Jasa Pengiriman Barang pada E-Commerce - Yemima Prasetyawati Cibro; Ari Setiawan (Jurnal Serambi Engineering, 2024)
Since the Covid-19 pandemic, the online sales business has grown rapidly, especially through e-commerce applications. E-commerce has become popular because it offers a variety of products at different prices and is often cheaper than direct sales. Prices in e-commerce are affected not only by the price of the goods, but also by service charges, shipping costs and other fees. Well-managed shipping costs are important so that buyers, sellers and applications all benefit. The number of shipping services available in e-commerce requires analysis to determine the best shipping service. This research aims to compare the best shipping services as a reference for sellers and buyers. This research examines how the e-commerce system selects automated shipping services and analyses whether the selection is optimal based on the category of goods, size, shape and distance. The selection of delivery services is modelled with a neural network to describe different possibilities based on the given criteria. The results show that the optimal use of delivery services is determined by handling according to category, size, shape, distance and special conditions. E-commerce should further improve the benefits of delivery services through better website connectivity and digital services.